VD_FINDINFO HC / 2012 / 752 vom 9. Januar 2013 - VD Tribunal cantonal (2013)
DIVORCE, LIQUIDATION DU RÉGIME MATRIMONIAL, VERSEMENT ANTICIPÉ, PRÉVOYANCE PROFESSIONNELLE | 125 CC, 133 CC, 197 CC, 198 CC, 207 CC, 215 CC, 285 CC